Defence Against Desiccation and Predation in Lophyohylini Casque-Headed Tree Frogs - César Alexandre; Pedro L. Mailho-Fontana; Bianca C. L. F. Távora; Marta M. Antoniazzi; Carlos Jared (Toxins, 2025)
Casque-headed tree frogs (Lophyohylini) can have a very large and distinctive head characterised by hyperossification of their cranial skin. This type of skull was primarily associated with phragmosis, a behaviour in which the frog enters holes backwards and seals them with its head to prevent water loss in challenging environments. Further investigations revealed that hyperossification also gives rise to bony spines interspersed with skin poison glands. These peculiar anatomical features of the head make it challenging for predators to prey on the frogs in phragmosis. When bitten on the head, the bite pressure causes the spines to cross the poison glands, allowing the injection of toxins into the predator’s mouth. We studied the head morphology of different Lophyohylini species along with some characteristics of their cutaneous poison, both in the field and in the laboratory. These frogs exemplify distinct chemical defence strategies, highlighting the differences between venom and poison. Notably, some species can cause self-poisoning in predators by injecting poison (in this case, venom) through their head spines, similar to the use of fangs by snakes.